2023
DOI: 10.1002/alz.12901
|View full text |Cite
|
Sign up to set email alerts
|

The worldwide costs of dementia in 2019

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
81
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(81 citation statements)
references
References 26 publications
0
81
0
Order By: Relevance
“…This review identified that mHealth applications were mainly developed in high-income countries. Although 96% of people with dementia are cared for in their homes by informal carers,7 LMICs pay only 10% of the cost of the social care sector in dementia, including the cost of the residential, nursing home or long-term care facilities 79. Social care costs in high-income countries are around 40% 79.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review identified that mHealth applications were mainly developed in high-income countries. Although 96% of people with dementia are cared for in their homes by informal carers,7 LMICs pay only 10% of the cost of the social care sector in dementia, including the cost of the residential, nursing home or long-term care facilities 79. Social care costs in high-income countries are around 40% 79.…”
Section: Discussionmentioning
confidence: 99%
“…Although 96% of people with dementia are cared for in their homes by informal carers,7 LMICs pay only 10% of the cost of the social care sector in dementia, including the cost of the residential, nursing home or long-term care facilities 79. Social care costs in high-income countries are around 40% 79. In light of a paucity of community-based dementia services in LMICs,80 previous studies found that informal carers of people with dementia in these countries had shown a lack of knowledge and the need for support systems or services 81–83.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Wimo and colleagues reported the worldwide cost of dementia as $422 billion, with $142 billion (34%) spent on informal care. 7 A more recent study using a similar methodology estimated the cost of dementia in the Arab world in 2009 to range from $4.2 billion to $6.7 billion, with dementia costs accounting for over 0.75% of the total gross domestic product (GDP) in Mauritania, Iraq and Egypt, whereas the economic burden for the Gulf Cooperation Council was estimated at less than 0.25% of the GDP. 8 A recent study by Wimo et al found that the annual global societal costs of dementia in 2019 were US $1313.4 billion for 55.2 million people with dementia.…”
mentioning
confidence: 99%
“…8 A recent study by Wimo et al found that the annual global societal costs of dementia in 2019 were US $1313.4 billion for 55.2 million people with dementia. 7 These costs included direct medical costs (US $213.2 billion, 16%), direct social sector costs such as long-term care (US $448.7 billion, 34%), and informal care costs (US $651.4 billion, 50%). This research showed that although the majority of people with dementia live in low- and middle-income countries, the highest total and per-person costs are observed in high-income countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation